The design of a single seater helicopter rotor Hub [electronic resource] - 458221 Raam Kumar Karuppiah (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2006